IGNITE 2016 STRENGTHENS USM-TUT COOPERATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 2 February 2016 – The Third International Conference of Global Network for Innovative Technology 2016 or IGNITE 2016, jointlyorganised by Universiti Sains Malaysia (USM) through the School of Materials and Mineral Resources Engineering (PPKBSM) and Toyohashi University of Technology (TUT) has enhanced the existing relations between the two educational institutions and also between Malaysia and Japan.